Universities of the Caribbean region--Struggles to democratize: An annotated bibliography - Waggoner, Barbara Ashton (G. K. Hall & Co., 1986)
An annotated bibliography on universities in the Caribbean region for the period since World War II is presented. The focus is on access to universities. For book citations, each annotation contains the author's name, publication title, place of publication, publisher, date, and number of pages. Journal references consist of author, title of article, name of journal, volume number, date, and page numbers. Newspapers, monographs, and other periodicals are also included. The first section, which covers 329 publications, provides general coverage on universities. Annotations are also provided on 172 publications on The University of the West Indies (UWI). The remainder of the bibliography covers countries/areas--Colombia (83), Costa Rica (90), Cuba (166), Dominican Republic (96), French Antilles (59), Guyana (55), Haiti (16), Honduras (25), Mexico (38), Netherlands Antilles (21), Nicaragua (74), Panama (75), Puerto Rico (83), U.S. Virgin Islands (7), and Venezuela (213)
Keywords: Universities